Physiological and Oxidative Effects of Coumarin Derivatives in Copper-Stressed Maize - Yetissin, F.; Yasar, M. (Pleiades Publishing Ltd, 2026)
Copper (Cu) accumulation is an important abiotic stress factor that increases oxidative damage and limits production by exerting pressure on water relations and photosynthetic pigments in plants. To the best of our knowledge, the effects of synthetic coumarin-sulfonate derivatives on antioxidant defense and phenylpropanoid metabolism in maize seedlings under copper stress have not been previously reported. This study evaluated the regulatory role of 4-methyl-2-oxo-2H-chromen-7-yl 2,5-dichlorobenzenesulfonate (MCDS; 0.9 mM), a synthetic coumarin-sulfonate derivative, on the antioxidant defense system and phenolic metabolism in maize (Zea mays L.) seedlings under copper stress (0.5 mM CuSO4 & centerdot;5H2O). Relative water content, photosynthetic pigments, internal leaf Cu accumulation, H2O2 and MDA, proline, antioxidant enzyme activities, and selected phenolic compounds were analyzed to comprehensively reveal the stress response at physiological and metabolic levels. The findings showed that MCDS pre-treatment increased photosynthetic pigments and proline accumulation without significantly altering RWC; it reduced internal Cu load and H2O2 and MDA levels. Antioxidant defense was particularly enhanced through peroxidase-based components; increases in GPX and APX activities were observed. Furthermore, a selective reprogramming of phenylpropanoid metabolism was detected. The results indicate that MCDS is a candidate regulatory agent/biostimulant that enhances tolerance to Cu stress through physiology-metabolism integration and has agricultural applicability.
Keywords: Zea Mays; Oxidative Stress; Coumarin-Sulfonate; Heavy Metal Toxicity (Cu); Antioxidant Defense System; Phenolic Compounds